Cobertura vegetal do Municipio de Taquaritinga, SP, Antes da expansao da cultura da cana-de-acucar. - Politano, W.; Corsini, P. C.; Amaral, C.; Teixeira, C. A. (My University, 1984)
Occurrence and distribution of 12 natural and anthropic communities were mapped.-from English summary
Vegetal cover of Taquaritinga Municipal Area, Sao Paulo, before sugar cane culture expansion
Keywords: photointerpretation.; soil occupation; vegetal cover